PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA HUKUM NEWTON UNTUK SISWA SMP MUHAMMADIYAH 4 MALANG - Nur Hasanah; Nur Subeki; Ary Dwi Astuti (Politeknik Negeri Sriwijaya, 2021)
Conceptual understanding of basic science such as physics is very important for a secondary school student. This community service program aims to improve students' understanding of Newton's law. Several learning media in the form of experimental tools have been designed in such a simple way that students can observe Newton's law phenomena through these experimental tools as well as on objects that are around. Based on the results of the assessment carried out, after the implementation of this program students' understanding of the concept of Newton’s law has increased. This is obtained by the increasing percentage of correct answers given by the students and students answering questions with more confidence.